High-Speed Rail in Tourism:: Demand Segments and Factors of Their Potential Transition to Alternative Modes of Transport - Šauer, Martin; Novotná, Markéta; Holešínská, Andrea; Vystoupil, Jiří (Ekonomický časopis/Journal of Economics, 2024)
This paper aims to investigate the factors which determine the willingness of visitors to switch to more environmentally friendly transport modes on touristoriented journeys in the Czech Republic. The proposed model of the hypothetical shift to a high-speed rail (HSR) considers personal and travel characteristics, the role of environmental attitudes, and previous experience with various transport modes. Data entering the model were obtained through a questionnaire among visitors in three key Czech hubs of the proposed HSR. The sample of 1,800 respondents was selected using a combination of random sampling and a quota applied to the length of stay and nationality. Using the Kruskal-Wallis test and subsequent contingency analyses, strong relationships were identified between train users and their willingness to use HSR. Environmental attitudes led to a strong preference for HSR. Similarly, the time spent on the journey and its purpose affected the willingness to switch to HSR.